The Legal Force Of The Deed Of Sale And Purchase Of Land On Congenital Property Between Husband And Wife - Restu Adhi Murti; Rafli Dwianto; Dina Rachmatika; Sigit Gunawan; Siska Karina (Journal Of Social Science (JoSS), 2024)
Land sale and purchase is an important transaction carried out to obtain rights to land. Land is one of the most valuable assets and has the potential to generate profits in the future. Land is becoming increasingly valuable because land is increasingly scarce, over time and the increasing human population, land prices continue to increase. This makes the business of buying and selling land an investment class that is definitely promising for everyone, ranging from housing, business premises, agriculture, to investment. Therefore, the process of buying and selling land and similar actions must be carried out carefully and in accordance with applicable legal provisions. However, many people do not understand the importance of the procedures for transferring land rights in Indonesia regulated in various laws and regulations. As happened in the journal to be discussed, where there was a sale and purchase between husband and wife that had been made AJB before the Temporary Land Maker Official. Where this agreement violates the objective requirements according to the Civil Code, resulting in the agreement being “null and void”. In this method we use a normative juridical method which is a library law research with an approach that is carried out using reviewing the main legal material focusing on analyzing regulations, doctrines, and legal principles related to the transfer of land rights.